(untitled) (Annals of Medical Research, 2023)
Aim: The blood urea nitrogen to serum albumin ratio (BAR) is a biomarker of acute pulmonary embolism, pneumonia, critical illness, and prognostic mortality in geriatric patients. Hospital stay of patients with acute cholecystitis is prolonged according to the severity of the disease. We evaluated the predictive ability of BAR for prolonged hospital stay in acute cholecystitis. Materials and Methods: This study was designed retrospectively and evaluated data collected at an emergency department from January 5, 2022, through April 5, 2022. Patients stayed in the hospital for eight days or longer were categorized as having a prolonged hospital stay, while those staying for seven days or less were considered to have an expected hospital stay. The receiver operating characteristic assessment was undertaken to establish the extent to which the investigated variables predicted prolonged hospital stay. Results: The study was conducted over the data of 220 patients. The mean age (25th-75th percentile) was 59.0 (43.8-71.0) years, and 109 (50 %) patients were female. During the one-month follow-up, four (2 %) patients died. In total, 86 patients underwent surgery. The odds ratio for predicting prolonged hospital stay was found to be 4.88 [95% confidence interval (CI): 1.66-14.37, p=0.002] for BAR, 2.81 (95% CI: 1.36-5.78, p=0.004) for blood urea nitrogen, and 0.13 (95% CI: 0.04-0.38, p<0.001) for albumin. Conclusion: The BAR calculated during the initial presentation to the emergency department can anticipate extended hospital stays in patients with acute cholecystitis.